Experimental Study on Anti-body effects of Anti-BV on the Bee Venom Herbal Acupuncture - Ki Rok Kwon; Kwang Ho Lee; Won Pil Park (Journal of pharmacopuncture, 2005)
Objectives : To observe physiological anti-body effects of anti-BV, acute toxic response, measurement of LD50, and the effects of anti-body were evaluated. Methods : LD50 of Anti-Bee Venom were measured, and to analyze acute toxic responses, weight, and the anti-body effects various concentrations of Anti-BV were diluted and the survival rate was measured. Cell blood count (CBC), liver, spleen, and kidney pathologies were observed from the histological aspects. Results : Experiment was conducted to observe Anti-BV as the anti-body to the bee venom and the following results were obtained: 1. Anti-BV was injected intraperitoneally and no toxic responses were witnessed. All of the experiment subjects stayed alive during the experiment, making LD50 analysis impossible. 2. Anti-BV was injected intraperitoneally in mice and no significant weight changes were measured between the control group and the experiment groups. 3. Measuring the concentration dependent survival rate, the highest survival rate was at the concentration of 1.25×102mg/kg(1/2.000) for Anti-BV. 4. No particular results were shown in the CBC test. 5. Observation of changes in the organ tissues, Anti-BV was found to suppress blood stasis in the liver and inhibit necrosis of the cells. Conclusion : Above results suggest that Anti-BV doesn't cause any toxic responses in the body and works as an anti-body to the bee venom. Further studies must be followed to secure the findings.